2022
DOI: 10.1002/jcla.24342
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasmid‐mediated quinolone resistance genes among clinical isolates of Klebsiella pneumoniae in southwest Iran

Abstract: Background Extensive and inappropriate use of quinolones has led to growing resistance rates to these broad‐spectrum antibiotics. The present study purposed to investigate the prevalence of plasmid‐mediated quinolone resistance (PMQR) genes in Klebsiella pneumoniae clinical isolates. Method Ninety‐two non‐repetitive K. pneumoniae clinical isolates were confirmed by standard microbiological methods. Antibacterial susceptibility of isolates toward seven agents from the quinolone family was evaluated by the disc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
2
2
Order By: Relevance
“…Our result for ciprofloxacin resistance in K. pneumoniae isolates was (40.0%), and for levofloxacin was (50.0%), which were not in agreement with Jomehzadeh et al [ 23 ] who showed different resistance ratios for ciprofloxcin (18.5%) and for levofloxacin (30.4%).…”
Section: Discussioncontrasting
confidence: 99%
“…Our result for ciprofloxacin resistance in K. pneumoniae isolates was (40.0%), and for levofloxacin was (50.0%), which were not in agreement with Jomehzadeh et al [ 23 ] who showed different resistance ratios for ciprofloxcin (18.5%) and for levofloxacin (30.4%).…”
Section: Discussioncontrasting
confidence: 99%
“…The study results of Salimbahrami et al showed that 47 (52%), 22 (25%), and 21 (23%) K. pneumoniae isolated from hospitals in Sari (northern Iran) contains the qnr B, qnr A, and qnr S genes, respectively [ 16 ]. In another study from southwestern of Iran by jomehzadeh et al, ciprofloxacin resistance was lower than our results while qnr A, qnr B, and qnr S were detected in (12%), (24%), and 17% of K. pneumonia isolates [ 23 ]. In the following, studies that reported results similar to ours are reviewed.…”
Section: Discussioncontrasting
confidence: 60%
“…In the following, studies that reported results similar to ours are reviewed. In a study conducted by Malek Jamshidi et al, at Yazd central laboratory, the qnr A gene was not detected in any of the K. pneumoniae strains, and the qnr B gene (25%) was identified as dominant [ 23 ]. In a study from India, 22% of isolates possessed both qnr B and qnr S genes, while the qnr A gene was not detected in any strains [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caution should be taken when interpreting those data to be the result of the development of resistance, tolerance or adaptation to an investigated compound. In general, measures in global healthcare have to be taken, since recent reports indicate growing resistances also for the last-resort antibiotics like carbapenems [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%